2021
DOI: 10.3390/ma14051216
|View full text |Cite
|
Sign up to set email alerts
|

Selected Properties of Formaldehyde-Free Polymer-Straw Boards Made from Different Types of Thermoplastics and Different Kinds of Straw

Abstract: This research investigated the effects of different thermoplastics types and different kinds of straw on selected properties of polymer-straw boards. Polyethylene, polyethylene, and polystyrene of virgin and of recycled origin were used for bonding the boards. Three kinds of straw were used: rape (Brassica napus L. var. napus), triticale (Triticosecale Witt b m.), and rye (Secale L.). Five-layer polymer-straw boards were produced. The obtained boards differed in both the materials they were made of and the moi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Mainly WPC is manufactured by methods used in the plastic industry. The exciting approach is flat pressing, which was used by numerous researchers [ 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. The OSB or particleboard with polymer addition in inner layers was characterized by better physical properties, which maintained good mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mainly WPC is manufactured by methods used in the plastic industry. The exciting approach is flat pressing, which was used by numerous researchers [ 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. The OSB or particleboard with polymer addition in inner layers was characterized by better physical properties, which maintained good mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous research, we investigated the effect of various types of straw (rye, triticale, and rape) and various type of thermoplastics (HDPE, low-density polyethylene (LDPE), polystyrene (PS), and PP) on the properties of five-layer boards [ 31 ]. The results showed that the properties of the obtained boards strongly depended on both kinds of the polymer and straw used [ 31 ]. The research described by Mihai et al [ 38 , 39 ] indicated that triticale straw has great potential in the production of thermoplastic composites.…”
Section: Introductionmentioning
confidence: 99%
“…The growing demand for eco-friendly wood-based panels with lower environmental footprints and reduced hazardous emissions of volatile organic compounds, such as free formaldehyde from the finished wood composites, have imposed new stricter regulations and requirements on both researchers and industrial practice, related to the development of sustainable, "green" composites [1][2][3][4][5]. The production of fiberboards, with an estimated global production of more than 104 million m 3 in 2020, is the second largest worldwide, surpassed only by the production of plywood [6].…”
Section: Introductionmentioning
confidence: 99%
“…The harmful formaldehyde released from wood composites can be reduced by adding formaldehyde scavengers to conventional adhesive systems, through the surface treatment of finished wood composites, or by using novel biobased wood adhesives as environmentally friendly alternatives to traditional thermosetting resins [ 39 , 40 , 41 , 42 , 43 ]. Another alternative to formaldehyde-based adhesives is the manufacture of binderless wood-based panels, since wood represents a natural polymeric material abundant in lignocellulosic constituents, such as cellulose, hemicelluloses, and lignin [ 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ].…”
mentioning
confidence: 99%